On the employability of the senior high school graduates: Evidence from the labor force survey - Aniceto C. Orbeta; Maropsil V. Potestad (Philippine Institute for Development Studies (PIDS), 2020)
Continuing from the Institute's 2018 study on the SHS and the labor market which interviewed graduating SHS students and HR managers of firms about their perspectives on the prospects for employment, this study intends to gauge the actual performance of the SHS graduates in the labor market. Entry into the labor market is considered as one of the possible exits of SHS graduates. Given the first batch of SHS graduates in April 2018, this study utilizes eight rounds of Labor Force Survey (LFS) from July 2018 to April 2020. Labor market outcomes of SHS graduates (G12) are compared to their peers - G10 and second-year college completers. To improve comparability, the paper uses a multi-valued treatment effect estimation (i.e., Inverse Probability Weighting with Regression Adjustment (IPWRA)) with each of the education outcome as treatment and utilizing individual and household characteristics. The results confirm the results in the earlier study that only a small proportion (a little over 20%) enter the labor force and most of them (more than 70 percent) continue with their education. The estimations also find a mixed result with SHS graduates sometimes performing better and sometimes poorer relative to their peers in terms of labor market outcomes. These suggest that there is a need to re-examine employment and entrepreneurial objective SHS given the expressed and realized propensity of SHS graduates to continue with their education rather than entering the labor market. There is also a need to continue to examine and validate the effectiveness the work preparation component of the SHS curriculum. Furthermore, there is a need to continue working with employers informing and demonstrating to them what SHS graduates can do and eventually clearly defining the right niche for them in the labor market. Finally, this calls for continued close monitoring and generating empirical evidence to help understand the role of SHS graduates in the labor market.
Keywords: 330; senior high school; K to 12; basic education; labor market; employability of SHS graduates; multivalued treatment effects